Implementasi Multiple Attribute Decision Making Dalam Pemilihan Distributor Terbaik Menggunakan Metode TOPSIS - Rillya Arundaa; Aditya Lapu Kalua (Jurnal Ilmiah Computer Science, 2023)
The Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method is a technique in multi-criteria analysis that plays a role in assisting the decision-making process. The tool is designed to determine the best alternative from a set of options based on predetermined criteria. The TOPSIS method helps companies manage risk and maximize profits in cooperation with distributors. The results of the ranking of the selection of the best distributors who get rank 1 with a value of 0.464 are CV Tiga Bintang Distributors, rank 2 with a value of 0.419 are CV Ardimas Distributors, rank 3 with a value of 0.4 are CV Diamond Distributors, rank 4 with a value of 0.325 are CV Agung Jaya Distributors, and rank 5 with a value of 0.256 are CV Mandiri Jaya Distributors.